Key Determinants Of Citizens’ Behavioural Intentions Towards Using E-government Services’ Portal In Palestine - Abdalla, Rania Ahmad Mustafa (2023)
With the internet era, governments are using the Information and Communication Technologies (ICT) to meet their citizens’ expectations by adopting new means for service delivery that break the organizational boundaries by transforming to electronic governments (e-governments). However, citizen's acceptance of these services is at a low rate in many countries. Recently, Palestinian government has launched its e-government services’ portal. The aim of this study is to investigate the factors that influence Palestinians behavioral intention towards the use of e-government services’ portal. It integrates an extended Unified Model of Electronic Government Adoption (UMEGA) in which a multidimensional perceived risk construct is used with trust in e-government services’ portal and its antecedents, Safety needs of the Palestinians, and Unified-Access point as potential determinants of citizens’ behavioral intention to use the e-government services’ portal. The study is of a quantitative nature, a structured questionnaire with quota and purposive sampling technique was used to collect the data from the Palestinian citizens who live in West Bank and intend (potential users) to use the e-government services’ portal were 415 valid responses were collected and analyzed using PLS-SEM. The findings revealed that performance expectancy, opportunity cost risk, trust in e-government services portal, safety needs, and unified access points are the main determinants of citizens’ attitudes.